Seasonal Diversity of Birds in Nagarjun Forest of Shivapuri Nagarjun National Park, Kathmandu, Nepal - Jha, Praveen Kumar (Tribhuvan University Journal, 2020)
Nagarjun forest of Shivapuri Nagarjun National Park plays a significant role in the conservation of avifaunal diversity, but there are very few studies on birds of such local biodiversity hotspots in Nepal. The objective of the present study was to obtain information on seasonal diversity, species richness and relative abundance of birds in Nagarjun forest. The study was carried out from August 2019to June 2020 covering two seasons (autumn and spring). A total of 97 species of birds belonging to 10 orders and 42 families were recorded from three trails. Total22 Mackinnon’s lists were produced resulting 97 bird species recorded from entire field survey. Passeriformes was recorded as the most dominating order represented by 69 species. Mackinnon’s listing and direct observation methods were used to survey birds and Shannon-Weiner diversity index was used for data analysis. Relative abundance showed that most of the species were rare (54%) followed by uncommon (20%), very common (15%) and common (11%). Shannon-Weiner diversity index showed higher value for spring (H = 3.895) than autumn (H =3.807) and evenness was also higher in spring (E= 0.899) than autumn (E = 0.887).The result indicated higher species richness in spring with 76 species than autumn with 73 species. Based on the Shannon–Weiner index, the overall species diversity was highest in the trail III.